2022
DOI: 10.2196/16996
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Experience of Tapentadol Nonmedical Use: Mixed Methods Study

Abstract: Background The prevalence of abuse, diversion, and web-based endorsement of tapentadol (extended-release [ER], immediate-release [IR]) has been characterized as low compared with other prescription opioids. Little is known about individual experience with tapentadol nonmedical use (NMU). Objective This study aims to pilot web-based survey technologies to investigate the motivation for tapentadol NMU, sources of procurement, routes of administration, tam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…However, researchers have previously used Pinterest and TikTok to study portrayals of drugs other than opioids (155)(156)(157)(158)(159)(160)(161)(162). Researchers have used Bluelight in the context of recruiting participants for studies related to opioid use (163,164). Our PubMed query returned no results related to opioid research for LinkedIn.…”
Section: Prior Use In Research Literaturementioning
confidence: 99%
“…However, researchers have previously used Pinterest and TikTok to study portrayals of drugs other than opioids (155)(156)(157)(158)(159)(160)(161)(162). Researchers have used Bluelight in the context of recruiting participants for studies related to opioid use (163,164). Our PubMed query returned no results related to opioid research for LinkedIn.…”
Section: Prior Use In Research Literaturementioning
confidence: 99%
“…Очень интересные результаты веб-опроса, посвящённого немедицинскому применению тапентадола, представлены в статье Vosburg Suzanne K, Dailey-Govoni T, Beaumont J et al [26] [27]. Сообщения собирали с помощью исследовательской программы веб-мониторинга системы наблюдения за злоупотреблениями, диверсификациями и зависимостью.…”
Section: результатыunclassified
“…A study with occasional opioid users showed that, unlike tramadol, therapeutic doses of tapentadol led exclusively to positive subject-rated effects, with faster onset and offset than other opioids, which may contribute to a greater frequency of use [ 28 , 29 ]. A recent web-based survey on tapentadol non-medical use revealed that, besides pain relief, it is consumed for multiple psychotropic effects, including relaxation, reduction in depression or anxiety, and getting high; a subgroup of participants even reported hallucinogenic side effects at higher doses [ 30 ]. Such potential to induce physical and psychological dependence, supported by rewarding and reinforcing effects comparable to those of morphine, underpinned its classification as a Schedule II substance in the USA [ 7 , 28 ].…”
Section: Introductionmentioning
confidence: 99%